Acts as Kerygma: lalein ton logon - Holladay, Carl R. (New Testament studies, 2017)
This essay argues that Acts is essentially kerygmatic in its literary texture and purpose. It assumes that literary purpose, even genre to some extent, can be determined by examining how language is used in two respects: (1) through the authorial voice of the narrative, and (2) by the direct speech of characters within the story. This is especially the case when there is a strong convergence in the pattern of usage in the narrative voice and the dialogical voice. Three literary aspects are investigated: (1) kerygmatic vocabulary, (2) the speeches, and (3) the expression ho logos tu theu/ho logos tu kyriu. The operative kerygmatic vocabulary in Acts is displayed in two appendices containing statistical information comparing Lukan usage with other NT writings.